The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fonc.2021.796152
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SREBP-1 Activation by a Novel Small-Molecule Inhibitor Enhances the Sensitivity of Hepatocellular Carcinoma Tissue to Radiofrequency Ablation

Abstract: Radiofrequency ablation (RFA) is an important strategy for treatment of advanced hepatocellular carcinoma (HCC). However, the prognostic indicators of RFA therapy are not known, and there are few strategies for RFA sensitization. The transcription factor sterol regulatory element binding protein 1 (SREBP)-1 regulates fatty-acid synthesis but also promotes the proliferation or metastasis of HCC cells. Here, the clinical importance of SREBP-1 and potential application of knockdown of SREBP-1 expression in RFA of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Although research and development of small molecule inhibitors of SREBP-1 is necessary, the number of existing inhibitors (such as fatostatin, FGH10019, betulin, and PF-429242) is small and the reports are few, and they have not entered clinical application ( Kamisuki et al, 2011 ; Zou et al, 2021b ; Wang T. B. et al, 2021 ; Ren et al, 2021 ). In addition to these, a recent report by Zou et al (2021) found a relationship between the expression level of SREBP-1 in HCC tissues and the prognosis of HCC RFA, and used a novel small molecule inhibitor of SREBP-1 in combination with RFA to achieve a better anti-tumor effect on HCC ( Trott and Olson, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although research and development of small molecule inhibitors of SREBP-1 is necessary, the number of existing inhibitors (such as fatostatin, FGH10019, betulin, and PF-429242) is small and the reports are few, and they have not entered clinical application ( Kamisuki et al, 2011 ; Zou et al, 2021b ; Wang T. B. et al, 2021 ; Ren et al, 2021 ). In addition to these, a recent report by Zou et al (2021) found a relationship between the expression level of SREBP-1 in HCC tissues and the prognosis of HCC RFA, and used a novel small molecule inhibitor of SREBP-1 in combination with RFA to achieve a better anti-tumor effect on HCC ( Trott and Olson, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…N-Arachidonoyl dopamine, a typical representative of N-acyl dopamines, can inhibit breast cancer cell migration, EMT, and stemness and cause decreased cholesterol biosynthesis by inhibiting SREBP-1, its key targets, and endoplasmic reticulum kinase 1/2 (ERK1/2) pathways ( 151 ). A novel small-molecule, SI-1, 1-(4-bromophenyl)-3-(pyridin-3-yl) urea inhibits aerobic glycolysis and enhances the antitumor effect of radiofrequency ablation in the HCC cells and xenograft tumors via inhibition of SREBP-1 activation ( 152 ). The treatment of docosahexaenoic acid, but neither n-6 PUFA arachidonic acid nor oleic acid, can inhibit the levels of the precursor of SREBP-1 and its mature form, and FASN is induced by estradiol and insulin to mediate breast cancer proliferation, which is the result from reduced phosphorylated Akt, not from ERK1/2 phosphorylation ( 153 ).…”
Section: Targeting the Srebp-1 Signaling Pathway For Cancer Therapymentioning
confidence: 99%
“…Glucose administration to experimental animals affects the metabolic characteristics of HCC tissues and expression of proliferation-related factors ( Broadfield et al, 2021 ; Loong et al, 2021 ). Cellular metabolism of glucose and lipids is closely related, and important regulators such as the transcription factors sterol regulatory element-binding transcription factor 1 (SREBP-1) and SREBP-2 can also affect expression of glucose metabolism-related factors and cellular glucose metabolism ( Yin et al, 2019 ; Zou et al, 2021 ). Therefore, our results suggest that glucose (energy support) and a lipid emulsion (nutritional support) will improve the physical status of patients, but may also promote HCC in vivo .…”
Section: Discussionmentioning
confidence: 99%